Cationic DOPC–Detergent Conjugates for Safe and Efficient in Vitro and in Vivo Nucleic Acid Delivery. (2nd August 2016) - Pierrat, Philippe; Casset, Anne; Didier, Pascal; Kereselidze, Dimitri; Lux, Marie; Pons, Françoise; Lebeau, Luc
Abstract: The ability of a nonviral nucleic acid carrier to deliver its cargo to cells with low associated toxicity is a critical issue for clinical applications of gene therapy. We describe biodegradable cationic DOPC–C12 E4 conjugates in which transfection efficiency is based on a Trojan horse strategy. In situ production of the detergent compound C12 E4 through conjugate hydrolysis within the acidic endosome compartment was expected to promote endosome membrane destabilization and subsequent release of the lipoplexes into cytosol. The transfection efficiency of the conjugates has been assessed in vitro, and associated cytotoxicity was determined. Cellular uptake and intracellular distribution of the lipoplexes have been investigated. The results show that direct conjugation of DOPC with C12 E4 produces a versatile carrier that can deliver both DNA and siRNA to cells in vitro with high efficiency and low cytotoxicity. SAR studies suggest that this compound might represent a reasonable compromise between the membrane activity of the released detergent and susceptibility of the conjugate to degradation enzymes in vitro. Although biodegradability of the conjugates had low impact on carrier efficiency in vitro, it proved critical in vivo. Significant improvement of transgene expression was obtained in the mouse lung tuning biodegradability of the carrier. Importantly, this also allowed reduction of the inflammatory response that invariably characterizes cationic‐lipid‐mediated gene transfer in animals. Abstract : Pulmonary delivery : Biolabile DOPC–C12 E4 conjugates were developed as nucleic acid carriers for in vitro and in vivo gene delivery. Their transfection efficiency and safety profile in mouse lung reflect their biodegradability and the surface active properties of the detergent released in situ. Thus, they might act as DNA carriers for gene therapy local administration through the airways.